Enhancing the Capacity of Tourism Awareness Groups in Climate Change Adaptation and Mitigation at the Tanjung Batu Mangrove Ecotourism, Sekotong Tengah Village, West Lombok Regency - Markum, Markum; Ichsan, Andi C; Aji, Irwan Mahakam Lesmono; Ashari, Agus Mulyadi (Unram Journal of Community Service, 2024)
Mangrove Ecotourism in Tanjung Batu is one of the unique tourist attractions on Lombok Island, featuring a scenic 11-hectare mangrove area with dense vegetation coverage. The site is equipped with several facilities, including a 417-meter wooden bridge, several gazebos, selfie spots, a homestay, and a café. The ecotourism management is handled by the Tourism Awareness Group (Pokdarwis) of Sekotong Tengah Village. This destination is quite popular, with no fewer than 300 tourists visiting each month. However, this area is prone to climate-related disaster risks such as tidal floods, strong winds, high waves, floods, and droughts. Additionally, the ecotourism management has mainly focused on physical aspects and lacks sufficient managerial skills for implementing a sustainable governance system. The proposed solution is to strengthen the Pokdarwis management to improve ecotourism governance, optimizing its potential to deliver greater social, economic, and environmental value while contributing to climate change adaptation and mitigation efforts. The conclusion from the community service activity is that to address these challenges, the community is committed to preserving the mangrove ecosystem, preventing disturbances from both internal and external factors, and managing ecotourism in a way that benefits the surrounding community by reducing climate-related disaster risks. Priority activities include mangrove rehabilitation and enrichment, beach cleanup, monthly management meetings, semi-annual evaluations, and promptly developing plans to strengthen the fishermen's economy through involvement in marine tourism packages